Screening and prevention of preterm birth: how is it done in clinical practice? - Roberta Bulsing dos Santos; Janete Vettorazzi; Marcos Wengrover Rosa; Ellen Machado Arlindo; Edimárlei Gonsales Valério (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: To ascertain how screening for preterm birth is performed among obstetricians working in public and private practice in a middle-income country. Methods: Cross-sectional study of 265 obstetrician-gynecologists employed at public and private facilities. An online questionnaire was administered, with items designed to collect data on prematurity screening and prevention practices. Results: The mean age of respondents was 44.5 years; 78.5% were female, and 97.7% had completed a medical residency program. Universal screening (i.e., by ultrasound measurement of cervical length) was carried out by only 11.3% of respondents in public practice; 43% request transvaginal ultrasound if the manual exam is abnormal, and 74.6% request it in pregnant women with risk factors for preterm birth. Conversely, 60.7% of respondents in private practice performed universal screening. This difference in screening practices between public and private practice was highly significant (p < 0.001). Nearly all respondents (90.6%) reported prescribing vaginal progesterone for short cervix. Conclusion: In the setting of this study, universal ultrasound screening to prevent preterm birth was used by just over half of doctors in private practice. In public facilities, screening was even less common. Use of vaginal progesterone in cervical shortening was highly prevalent. There is an unmet need for formal protocols for screening and prevention of preterm birth in middle-income settings.